2013
DOI: 10.1177/0269881112473789
|View full text |Cite
|
Sign up to set email alerts
|

Weight change by baseline BMI from three-year observational data: findings from the Worldwide Schizophrenia Outpatient Health Outcomes Database

Abstract: The aim was to explore weight and body mass index (BMI) changes by baseline BMI in patients completing three years of monotherapy with various first- and second-generation antipsychotics in a large cohort in a post hoc analysis of three-year observational data. Data were analyzed by antipsychotic and three baseline BMI bands: underweight/normal weight (BMI <25 kg/m²), overweight (25-30 kg/m²) and obese (>30 kg/m²). Baseline BMI was associated with subsequent weight change irrespective of the antipsychotic give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 26 publications
5
52
1
1
Order By: Relevance
“…Iloperidone, quetiapine, risperidone, paliperidone, sertindole, and zotepine confer an intermediate risk, whereas amisulpride, aripiprazole, asenapine, lurasidone, and ziprasidone are generally associated with small increases in body weight . A post hoc analysis of 4626 patients with schizophrenia, who had completed 3 years of naturalistic antipsychotic monotherapy with clozapine, olanzapine, quetiapine, risperidone, amisulpride, and oral and depot first‐generation antipsychotics , indicated that the mean weight gain was highest with olanzapine (4.2 kg) and lowest with amilsulpride (1.8 kg). Weight accrual was fastest during the first 6 months of treatment and, depending of the drug, 7–15% of patients moved from normal weight to the overweight or obese status .…”
Section: Resultsmentioning
confidence: 99%
“…Iloperidone, quetiapine, risperidone, paliperidone, sertindole, and zotepine confer an intermediate risk, whereas amisulpride, aripiprazole, asenapine, lurasidone, and ziprasidone are generally associated with small increases in body weight . A post hoc analysis of 4626 patients with schizophrenia, who had completed 3 years of naturalistic antipsychotic monotherapy with clozapine, olanzapine, quetiapine, risperidone, amisulpride, and oral and depot first‐generation antipsychotics , indicated that the mean weight gain was highest with olanzapine (4.2 kg) and lowest with amilsulpride (1.8 kg). Weight accrual was fastest during the first 6 months of treatment and, depending of the drug, 7–15% of patients moved from normal weight to the overweight or obese status .…”
Section: Resultsmentioning
confidence: 99%
“…The nutritional status of schizophrenia patients was previously measured using anthropometric parameters such as body weight and BMI, rather than through the use of multifaceted tools such as the MNA . However, it has been reported that a single indicator such as an anthropometric or biochemical parameter does not accurately reflect nutritional status in other chronic diseases; so, the determination of nutritional status using tools reflecting various aspects has been emphasized .…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional status of schizophrenia patients was previously measured using anthropometric parameters such as body weight and BMI, rather than through the use of multifaceted tools such as the MNA. 10,11,38 However, it has been reported that a single indicator such as an anthropometric or biochemical parameter does not accurately reflect nutritional status in other chronic diseases; so, the determination of nutritional status using tools reflecting various aspects has been emphasized. 23,26 The MNA is a multidimensional assessment tool including information on food intake due to appetite or swallowing difficulty, anthropometric measurements including weight loss, and physical and mental functions 21,22 and has been validated in patients with schizophrenia.…”
Section: Factors Related To Malnutrition In Community-dwelling Patimentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to first‐generation antipsychotics, second‐generation antipsychotics cause fewer extra‐pyramidal problems, but they present new challenges because they often lead to metabolic disorders. For example, risperidone increases food intake and induces weight gain, glucose intolerance, hypertriglyceridemia, and hyperprolactinemia . Previous research has suggested that risperidone induces weight gain by upregulating the expression of hypothalamic histaminergic H1 receptors and neuropeptide Y (NPY) .…”
Section: Introductionmentioning
confidence: 99%